Metabolome-Wide Association Study of the Relationship Between Habitual Physical Activity and Plasma Metabolite Levels. Issue 11 (31st July 2019) - Ding, Ming; Zeleznik, Oana A; Guasch-Ferre, Marta; Hu, Jie; Lasky-Su, Jessica; Lee, I-Min; Jackson, Rebecca D; Shadyab, Aladdin H; LaMonte, Michael J; Clish, Clary; Eliassen, A Heather; Sacks, Frank; et al.
Abstract: We identified plasma metabolites associated with habitual physical activity among 5, 197 US participants from the Nurses' Health Study (NHS), Nurses' Health Study II (NHS II), and the Health Professionals Follow-up Study (HPFS). Physical activity was assessed every 2–4 years via self-report questionnaires. Blood was collected in the NHS in 1989–1990, in NHS II during 1996–1999, and in the HPFS during 1993–1995. Metabolic profiling was conducted by liquid chromatography–mass spectrometry. Our study included 337 known metabolites, with 256 of them classified as lipids. We corrected for multiple testing by controlling the tail probability of the proportion of false positives (TPPFP) and accounted for correlated tests using bootstrapping. Physical activity was significantly associated with 20 metabolites after correction for multiple testing (TPPFP < 0.05), and positive associations were found for most of the metabolites, including 2 amino acids (citrulline and glycine), 4 cholesteryl esters (C18:2, C18:1, C16:0, C18:3), 8 phosphocholines (PCs) (C36:4 PC-A, C34:3 PC plasmalogen, C36:3 PC plasmalogen, C34:2 PC plasmalogen, C36:2 PC) and lysophosphatidylcholines (C18:2, C20:5, C18:1), and 3 phosphatidylethanolamines (PEs) (C38:3 PE plasmalogen) and lysophosphatidylethanolamines (C18:2, C18:1). We independently replicated the 20 metabolites among 2, 305 women in the Women's Health Initiative using 1993 data, and half of the metabolites were replicated. Our study may help identify biomarkers of physical activity and provide insight into biological mechanisms underlying the beneficial effect of being physically active on cardiometabolic health.